Les erreurs de droit dans l'exercice d'une compétence - Lemieux, Denis (Les Cahiers de droit, 1982)
In this paper, the author deals with the legal foundations of judicial control over errors of law allegedly committed by administrative authorities. The paper also considers the scope of error of law on the face of the record as a ground of review. More specifically, the author has examined all the decisions rendered by the Quebec Court of Appeal, the Federal Court, and the Supreme Court of Canada in 1980 and 1981 where there was an allegation of error of law. From this statistical analysis, the author describes and explains the different, and seemingly contradictory, results achieved by these different jurisdictions. The author adds some comments on the constitutionality of privative clauses excluding judicial review of non-jurisdictional errors of law.